Designing a Balanced Scorecard for Fitting the Requirements of Sustainability: Applied Study at the Iraqi Ministry of Education - Baghdad Education Directorate - Morad, Bayan Jowmer Maykan; Alsalmani, Qabas Abdulrazzaq Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to design balanced scorecards in accordance with the environmental, economic and social requirements for the directorate of education of Baghdad to achieve the sustainability of the educational institution. As designing and applying of balanced and sustainable scorecards ensures the integration of dimensions and issues of sustainability that fit the Iraqi educational institutions, in general, and Baghdad General Directorate of Education, in special. This allows the General Directorate of Education of Baghdad to identify strengths and weaknesses and to improve the efficiency of its resources through the evaluation of the strategic performance in Baghdad Directorate General of Education, by following the inductive approach in the theoretical part and the deductive approach for the practical aspect through analyzing the quantitative and descriptive data. The research has reached to some conclusions. The most important of these conclusions is that most research samples in this field do not use a modern management technology such as sustainable balanced scorecards, which in turn, integrate the requirements and dimensions of sustainability to assess its performance and to identify strengths and weaknesses, which in turn works to achieve the sustainable development of the General Directorate of Education of Baghdad.